Late respiratory sequelae of blunt chest injury: a preliminary report. Issue 3 (March 1981) - Hanning, C D; Ledingham, E; Ledingham, I M
Abstract : Eighty-six survivors of blunt chest injury were assessed for pre- and post-injury respiratory symptoms using a standardised questionnaire. A comparison was made between observed and expected symptom prevalence and lung function. Respiratory symptom prevalence after injury was greater than expected, 23 survivors (27%) claiming a persistent productive cough, 18 (21%) persistent wheezing, and 22 (26%) grade 2 dyspnoea. After injury persistent productive cough (p less than 0.05) and occasional wheezing (p less than 0.01) were more common among smokers and ex-smokers when compared with non-smokers. Mean forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) were not statistically different from expected values. We concluded that respiratory sequelae of blunt chest injury are common and that smokers and ex-smokers are at particular risk.